MASS TRANSFER KINETICS AND EFFECTIVE DIFFUSIVITIES DURING COCOA ROASTING - Y. M. BAGHDADI; C. L. HII (Journal of Engineering Science and Technology, 2017)
The current studies investigated the effects of temperature and moisture addition on the mass transfer kinetics of cocoa nibs during roasting. Experiments were carried out by roasting 500 gm of cocoa nibs inside an air ventilated oven at three temperature levels (120°C, 140°C and 160°C) under medium air flowrate for one hour. Two types of samples were prepared namely the raw and soaked nib samples. The soaked nib samples were prepared by soaking the raw nibs in 200 ml of water at room temperature for 5 and 10 hours. Mathematical modelling was carried out to model the mass transfer process using semi-empirical models. Modelling showed that both Page and two-term models were able to give close fitting between the experimental and predicted values. Effective diffusivity values were estimated in the order of magnitude of 10-5 m2/s for the mass transfer process. Results obtained from these studies fill the current knowledge gap on the mass transfer kinetics of cocoa roasting.